Characterization of mycotoxins from entomopathogenic fungi (Cordyceps fumosorosea) and their toxic effects to the development of asian citrus psyllid reared on healthy and diseased citrus plants. (December 2020) - Qasim, Muhammad; Islam, Saif Ul; Islam, Waqar; Noman, Ali; Khan, Khalid Ali; Hafeez, Muhammad; Hussain, Dilbar; Dash, Chandra Kanta; Bamisile, Bamisope Steve; Akutse, Komivi Senyo; Rizwan, Muhammad; Nisar, Muhammad Shahid; et al.
Abstract: Entomopathogenic fungi (EPF) produce multiple mycotoxins, which play an essential role in improving fungal pathogenesis and virulence. To characterize various mycotoxins from the crude methanol extract of Cordyceps fumosorosea, a major EPF against various insect pests, we performed ultra-performance liquid chromatography coupled to quadrupole time of flight mass spectrometer (UPLC-QTOF MS) technique, and all compounds were identified through molecular mass and formulae. Bassianolide was assessed against the nymphs and adults of Diaphorina citri reared on healthy and Huánglóngbìng (HLB)-diseased Citrus spp. Plants under laboratory conditions. Overall, 17 compounds were identified from the fungal extract and categorized into three groups, i.e. (1) alkaloids (Isariotins A-C), (2) peptides (Bassianolide, Beauverolides, Beauvericin A, Isaridins and Destruxin E) and (3) polyketide (Tenuipyrone). The detected beauverolides (B, C, F, I, Ja) from C. fumosorosea were novel mycotoxins, and their detection intensity was the highest in the fungal extract. Furthermore, bassianolide caused more than 70% and 80% mortality of D. citri nymphs and adults after two days of application, respectively. After three days of chemical application, all nymphal and adult populations of D. citri were killed by bassianolide. However, the mortality rates of both populations, nymphs and adults, were higher on HLB-diseased plants as compared to healthy plants. Graphical abstract: Image 1 Highlights: Seventeen mycotoxins were identified by mass and formulae via liquid chromatography-mass spectrometry. Mycotoxins were classified into three groups; 1) alkaloids, 2) peptides, 3) polyketide. Methanol extract of Cordyceps fumosorosea was enriched with novel beuverolides. Bassianolide caused more than 70% mortality of citrus psyllid within two days. Mortality of adult and nymph was higher on huanglongbing-diseased plants.